Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1001/jamacardio.2021.0669
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Biomarkers in the Early Discrimination of Type 2 Myocardial Infarction

Abstract: IMPORTANCERapid and accurate noninvasive discrimination of type 2 myocardial infarction (T2MI), which is because of a supply-demand mismatch, from type 1 myocardial infarction (T1MI), which arises via plaque rupture, is essential, because treatment differs substantially. Unfortunately, this is a major unmet clinical need, because even high-sensitivity cardiac troponin (hs-cTn) measurement provides only modest accuracy.OBJECTIVE To test the hypothesis that novel cardiovascular biomarkers quantifying different p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Even previous data demonstrated that cTn only provides limited discriminative value [4] , [5] , [8] , [9] . Some studies have suggested that this could be enhanced by the consideration of clinical findings and/or other biomarkers [10] , [11] , [12] , [13] . However, none of these approaches is generally acknowledged, and the differentiation of both NSTEMI types will likely remain cumbersome, in particular in patients with critical illness or known CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Even previous data demonstrated that cTn only provides limited discriminative value [4] , [5] , [8] , [9] . Some studies have suggested that this could be enhanced by the consideration of clinical findings and/or other biomarkers [10] , [11] , [12] , [13] . However, none of these approaches is generally acknowledged, and the differentiation of both NSTEMI types will likely remain cumbersome, in particular in patients with critical illness or known CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have demonstrated that hs-cTn concentrations themselves only provide limited discriminative value [ 23 , 30 32 ]. This could be enhanced by combinations with other cardiovascular biomarkers or advanced statistical modelling [ 23 , 30 , 31 , 33 ], none of which currently used in routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also suggest that the hs-cTn I/T ratio may be a clue for the clinically challenging distinction of type 2 MI from type 1 MI. Previous data have demonstrated that hs-cTn concentrations themselves only provide limited discriminative value [23,[30][31][32]. This could be enhanced by combinations with other cardiovascular biomarkers or advanced statistical modelling [23,30,31,33], none of which currently used in routine practice.…”
Section: Plos Onementioning
confidence: 99%
“…cTnT is unique to the myocardium and mainly exists in myofibrillar thin filaments. High levels of cTnT are closely related to myocardial hypoxia, ischemia, necrosis, and cardiac function decline, and the detection of cTnT has the advantages of high sensitivity and specificity, both in the early intervention and prognosis of acute MI have important value [ 35 ]. NT-proBNP is a cardiogenic neurohormone synthesized by ventricular myocytes.…”
Section: Discussionmentioning
confidence: 99%